2021
DOI: 10.3390/ijerph182312793
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Behaviour and Nutrition in Patients with COPD Treated with Long-Term Oxygen Therapy

Abstract: Background: It is the first study in Poland and one of the first in the world to assess the nutrition of patients with chronic obstructive pulmonary disease (COPD) treated with long-term oxygen therapy (LTOT). Methods: The study group consisted of 110 COPD patients treated with LTOT. Anthropometric measurements and spirometry were performed. The diet of patients was assessed using a 3-day nutrition diary. Results: When assessing the degree of airflow obstruction (FEV1% N) depending on the BMI in patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, other studies [ 7 , 8 ] showed that COPD patients with sarcopenia might have a higher BMI. Patients with COPD may exhibit a considerable loss in lean body mass (LBM) but store extra fat, resulting in a high BMI [ 42 ]. The Fat-Free Mass Index (Ffmi) is more suitable for assessing patients with COPD compared to healthy people due to long-term hormone use, leading to central obesity, which masks the presence of sarcopenia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies [ 7 , 8 ] showed that COPD patients with sarcopenia might have a higher BMI. Patients with COPD may exhibit a considerable loss in lean body mass (LBM) but store extra fat, resulting in a high BMI [ 42 ]. The Fat-Free Mass Index (Ffmi) is more suitable for assessing patients with COPD compared to healthy people due to long-term hormone use, leading to central obesity, which masks the presence of sarcopenia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appetite is frequently decreased related to both the disease's inflammatory process and increased work of breathing 12 . A recent evaluation in patients with COPD and long‐term oxygen therapy in Poland demonstrated from a 3‐day food record that in 51.8% of participants, energy consumption was less than the recommended standards 13 . A stepwise approach to nutrition management in COPD as is outlined by the British Association of Parenteral and Enteral Nutrition (BAPEN) includes a step for EN initiation if nutrition goals are not met with a combination of an oral diet and oral nutrition supplements 14…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%